Analýza výskytu enterobióz v České republice v letech 2018–2022 - Šimka, V; Špačková, M (Epidemiologie, mikrobiologie, imunologie, 2024)
AIM: Pinworm infection (known as enterobiasis or oxyuriasis) is one of the most common parasitic diseases globally and in the Czech Republic (CZ). The aim of this study is to analyse the available epidemiological data on the incidence of enterobiasis in the CZ from 2018-2022. METHODS: A descriptive analysis was done of enterobiasis (ICD-10 code B80) data reported to the electronic Infectious Disease Information System in the CZ from 2018 to 2022. Data processing and analysis were conducted using MS Excel 2016. Univariate and multivariate logistic regression analyses were performed to assess the association between the probability of hospitalization and categorical variables using STATA version 17. The ECDC Map Maker tool (EMMa) was used to create the incidence map. RESULTS: A total of 4,836 cases were reported during the study period, with an average annual incidence of 9.1 cases per 100,000 population. The highest number of cases occurred in 2019 (n = 1,174), and the lowest in 2021 (n = 780). The disease was most common in the paediatric population, with the highest average age-specific incidence rates observed in children aged 5-9 years (80.9 per 100,000 population) and 10-14 years (42.3 per 100,000 population). Of 14 administrative regions of the CZ, the Olomouc Region had the highest average annual incidence (28.7 per 100,000 population), while the Pilsen Region had the lowest (2.2 per 100,000 population). A total of 472 (9.8%) patients needed hospitalization, most of them in the categories 10-14 years (n = 200, 42.4%) and 5-9 years (n = 178, 38%). The highest hospitalization rate was found in the age group 75+ (36.4%). A significantly higher probability of hospitalization was found in the age groups 6-19 years and 65+ compared to working-age population with enterobiasis. A significantly lower probability of hospitalization was seen in 2020-2022 compared to 2019. No difference in the hospitalization rates was noted between genders. No enterobiasis-related death was reported during the study period. The disease occurs year-round. A decrease in reported cases was observed annually during the school summer holidays in July and August. Neither outbreak nor imported cases were noted. CONCLUSION: Given that enterobiasis is often asymptomatic, many cases are not captured in the surveillance system. The Czech prevalence data indicate that it mainly affects the paediatric population. Therefore, preventive measures and programs should primarily target children.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; lidé středního věku; enterobióza; kojenec; dítě; Child; Enterobiasis; Female; Aged; mladý dospělý; dospělí; senioři; lidé; hospitalizace; Enterobiasis – Enterobius vermicularis – oxyuriasis – parasitic diseases – epidemiology – children – Czech Republic – descriptive analysis; předškolní dítě; Adult; ženské pohlaví; Male; Hospitalization; Middle Aged; Adolescent; incidence; Incidence; Czech Republic; Aged, 80 and over; Young Adult; senioři nad 80 let; Česká republika; mužské pohlaví; Child, Preschool; mladiství